Sosialisasi Penerapan Google FormsSebagai Alat Penilaian Pembelajaran di SDN117 Pekanbaru - Indah Muzdaliifah; Dian Rianita; Elvira Asril (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The corona virus pandemic indirectly has a very significant impact on aspects of human life, especially in the education aspect. Every role holder in education, both teachers, students, parents, must be ready to carry out the 4.0 revolution where learning is carried out online. The purpose of this community service activity is to provide socialization and share knowledge about the use of an application that can facilitate teachers in the assessment system or learning assessment which is usually carried out in class using paper replaced by using sophisticated applications that can be downloaded for free on the internet. The use of the application in question is Google form. This application aims to facilitate teachers in the assessment of learning evaluation. This activity made a significant contribution so that it was beneficial for partners in this activity are the teachers of SDN 117 Pekanbaru.